Land-based wind energy cost trends in Germany, Denmark, Ireland, Norway, Sweden and the United States. (1st November 2020) - Duffy, Aidan; Hand, Maureen; Wiser, Ryan; Lantz, Eric; Dalla Riva, Alberto; Berkhout, Volker; Stenkvist, Maria; Weir, David; Lacal-Arántegui, Roberto
Highlights: International trend is for larger, taller wind turbines with lower specific powers. Capital costs fell by 10% to 1, 422€/MW over the period. Reduction of 33% in levelised cost of energy to 48€/MWh. Specific power, finance and capital cost account for 45%, 25% and 17% of reduction. Levelized cost of wind energy has fallen, but value has fallen proportionately more. Abstract: This paper presents work by the International Energy Agency's Task 26 'Cost of Wind Energy' on technological and cost trends in land-based wind energy in six participating countries (Denmark, Germany, Ireland, Norway, Sweden, United States) and the European Union between 2008 and 2016. Results indicate that there is a general trend towards larger, taller machines with lower specific powers resulting in higher capacity factors, despite small falls in new site wind resources in most countries, while wind project capital costs and project finance costs also fell. This resulted in an average levelized cost of energy (LCOE) fall of 33% for new projects to 48€/MWh at the end of the study period. Analysis of the components of levelized cost change indicated that changes in specific power, financing cost and capital cost accounted for 45%, 25% and 17% respectively of the estimated reduction. It is therefore important that trends in technological factors such as specific power are considered when assessing wind energy learning rates, rather than just capital costs, which has been the primary focus heretofore. While LCOEs have fallen, the value of wind energy has fallen proportionately more, meaning grid parity appears no closer than at the beginning of the study. Policymakers must therefore consider both the cost and value of wind energy, and understand the volatility of this gap when designing land-based wind energy policy measures.